Availability, attitudes and costs of selected dental services in a low-income country - Nyamuryekung'e, Kasusu Klint (fi=Turun yliopisto|en=University of Turku|, 2019)
ABSTRACT The aim of this study was to determine the availability of selected dental services, attitudes towards such services and economic factors associated with their utilization in a low-income country. Data utilized for this study was collected in two phases. Phase I was a survey of all dental facilities in four selected regions in Tanzania. The survey was administered to officers-in-charge of dental facilities and other dental practitioners working within these facilities. Phase II was a series of cross-sectional studies conducted among outpatients attending four selected regional hospitals in Tanzania. Data was collected using self-administered questionnaires. Dental materials and equipment were inconsistently available and only 3/28 studied dental facilities had all the seven investigated equipment fully functional and in use. The self-rated competency among dental practitioners ranged from 6.4 to 9.8 for all six procedures questioned, but equal scores between cadres were only for tooth extractions (9.7 vs. 9.1 respectively). Competencies for placing restorations were all rated lower by other cadres (p varied from <. 05 to < .001). Most of the patients had a negative overall attitude (-1.99) towards tooth filling treatment although those with previous tooth filling experience had positive attitudes (1.00). The mean willingness-to-pay (WTP) values for tooth filling (7,398 and 7,726 Tshs for anterior and posterior teeth, respectively) were higher (p < 0.001) than for tooth extraction irrespective of tooth type (5,448 and 6,188 Tshs, respectively). Being 45+ years increased the likelihood to offer lower WTP values. More than half (55%) of the patients would experience significant financial impacts as a result of their utilization of dental services. The findings clearly suggest that there are a multitude of factors that influence the observed dental treatment patterns being predominated by tooth extractions in Tanzania. Keywords: Willingness-to-pay, costs, dental services, attitudes, Tanzania

TIIVISTELMÄ Valikoitujen hammashoitopalvelujen saatavuus, niihin liittyvät asenteet ja käytön kustannukset vähävaraisessa maassa Tutkimus selvitti valikoitujen hammashoitopalveluiden saatavuutta sekä niihin liittyviä asenteita ja käyttöön liittyviä taloudellisia tekijöitä vähävaraisessa maassa. Ensin tehtiin kyselytutkimus kaikissa hammashoitopalveluja tarjoavissa yksiköissä neljällä valitulla tansanialaisella hallintoalueella näiden yksiköiden johtajien ja hammashoitoa antavien työntekijöiden keskuudessa. Toiseksi toteutettiin sarja poikkileikkaustutkimuksia kyselyin näiden neljän hallintoalueen avohoitopotilaiden keskuudessa. Kyselyissä selvitettiin valikoitujen hammashoitopalvelujen kustannuksia, hammashoitomateriaalien ja -laitteiden saatavuutta, hammashoidon työntekijöiden kokemia valmiuksia, potilaiden asenteita ja maksuhalukkuutta paikkaushoitoon sekä potilaille hammashoidosta aiheutuviin kustannuksia. Materiaaleja ja laitteita oli vaihtelevasti saatavilla. Vain kolmessa tutkitusta 28 hoitolasta kaikki seitsemän tutkimuksessa tarkasteltua laitetta olivat käytössä ja toimintakunnossa. Hammaslääkärien kokemat valmiudet toimenpiteisiin vaihtelivat (6,4–9,8) ja olivat saman tasoisia muiden ammattiryhmien kanssa vain poistoissa (9,7 vs. 9,1). Paikkausvalmiudet olivat alempia muilla ammattiryhmillä (p <0,05–<0,001). Useimmilla potilailla oli negatiivinen kokonaisasenne (-1,99) paikkaushoitoon. Heillä, joilla oli aiempaa kokemusta paikkaushoidosta, oli positiivinen asenne (1,00). Paikkaushoidon maksuhalukkuuden keskiarvot olivat huomattavasti korkeammat (7398 Tansanian shillinkiä (Tshs) etualueella ja 7726 Tshs taka-alueella) kuin hammaspoistojen maksuhalukkuuden (5448 Tshs etualueella ja 6188 Tshs taka-alueella, p<0,001). Hammashoitopalvelujen käyttö aiheutti yli puolelle (55 %) tutkituista potilaista merkittäviä taloudellisia vaikutuksia. Tulokset osoittavat selvästi, että Tansaniassa monet tekijät vaikuttavat hammashoitopalvelujen tuotantoon, jota hallitsevat hampaiden poistot. Avainsanat: Maksuhalukkuus, kustannukset, hammashoitopalvelut, asenteet, Tansania